Republic of Mozambique : Third Review Under the Policy Support Instrument; Staff Report; Staff Supplement; and Press Release. (IMF Staff Country Reports; Country Report ;, 2009)
This paper presents the staff report on the Republic of Mozambique's Third Review under the policy support instrument. Mozambique is vulnerable to the global financial crisis and economic slowdown. Lower import prices will help reduce inflation and likely benefit the trade balance. Lower export volumes and reduced private capital inflows are expected to reduce economic growth. The turbulence could also spread to the financial system despite its limited integration into global financial markets. The government is focusing on strengthening policy operations, giving special attention to the tax system and public financial management.